Verification of Survival Predictors in Elderly Patients with Myelodysplastic Syndrome from Outpatient Clinical Practice - Eva Kadlčková; Peter Rohoň; Tomáš Fürst; Libor Červínek; Anna Jonášová; Tomáš Šálek; Jiří Tesař; Yvetta Stavařová (International Journal of Gerontology, 2018)
Summary: Background: Myelodysplastic syndrome (MDS) is a clonal disorder affecting older persons. We aimed to analyze the effectiveness of the scoring systems and of the number of received red blood cell (RBC) units in predicting survival. Methods: The study included an unselected group of 73 patients with MDS who were diagnosed and treated in a single hospital over a period of 12 years. International Prognostic Scoring System (IPSS), revised IPSS (IPSS-R), WHO-Prognostic Scoring System (WPSS), Charlson Age-Comorbidity Index (CACI), and impact of performance status (PS) on overall survival (OS) and event free survival (EFS) were tested. The follow-up of received RBC units was conducted. Results: The median age at diagnosis was 69.5 years, the median CACI was 3.0. The median survival times of the group were 7.04 and 2.78 years for OS and EFS, respectively. The concordance values of the IPSS, IPSS-R and WPSS are 0.812, 0.892 and 0.889 for OS; 0.785, 0.847 and 0.827 for EFS. The comorbidity index and PS were the only auxiliary criteria when determining the risk and selecting the therapeutic approach in MDS patients. In transfusion-dependent unchelated patients, both OS and EFS were negatively influenced by both higher ferritin levels and the numbers of RBC units; however, the risk does not continue to increase after more than 20 RBC units are administered. Conclusions: IPSS-R is best suited as a predictor of survival. CACI and PS present auxiliary criteria for determining the risk. Number of received RBC units was detected as a significant predictor of survival. Keywords: chelation therapy, myelodysplastic syndrome, prognostic scoring system, transfusion